Microhabitat use of larval fish in a South Carolina Piedmont stream. Issue 1 (9th November 2022) - Bower, Luke M.; Peoples, Brandon K.
Abstract: Understanding habitat use and nursery areas of larval fish is a key component to managing and conserving riverine fishes. Yet, freshwater researchers often focus only on adult fishes, resulting in a limited understanding of the habitat requirements for the early life stages of freshwater fishes. The goal of this study was to quantify the larval fish microhabitat use of three fish families in Twelvemile Creek, a fifth-order tributary of Lake Hartwell (Savannah River basin) in the Piedmont ecoregion of South Carolina, USA. We used handheld dipnets to sample larval fishes along 20 equidistant transects spaced 10 m apart weekly from May to July 2021 along a 200 m stream reach. We also collected microhabitat data at each larval fish capture location. Most captured individuals were in the metalarval stage and were identified to the family level. A partial distance-based redundancy analysis indicated that water velocity contributed to changes in larval fish assemblage structure. Larval fishes occupied a subset of the available habitat that was characterized by low water velocity, non- Podostemum substrate, and shallow habitats close to the shore or bed rock structure. We also detected temporal patterns in larval fish counts, with peak Percidae and Leuciscidae counts in late July and the highest Catostomidae counts in late May–early June. Our results suggest that larval fishes select habitats with low water velocity and shallow habitats close to shore microhabitat characteristics, and that riffle-pool sequences may serve as a nursery habitat for Percidae, Catostomidae and Leuciscidae metalarvae. Graphical Abstract: UF0001